2013
DOI: 10.1088/0004-637x/773/1/44
|View full text |Cite
|
Sign up to set email alerts
|

STAR FORMATION AND GAS KINEMATICS OF QUASAR HOST GALAXIES ATz∼ 6: NEW INSIGHTS FROM ALMA

Abstract: We present Atacama Large Millimeter/submillimeter Array (ALMA) observations of the [C II] 158 µm fine structure line and dust continuum emission from the host galaxies of five redshift 6 quasars. We also report complementary observations of 250 GHz dust continuum and CO (6-5) line emission from the z=6.00 quasar SDSS J231038.88+185519.7 using the IRAM facilities. The ALMA observations were carried out in the extended array at 0. −4 , which is comparable to the values found in other high-redshift quasar-starbur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
638
5
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 403 publications
(714 citation statements)
references
References 80 publications
69
638
5
2
Order By: Relevance
“…The high-z points that show a deficit in this study tended to host an AGN. Wang et al (2013a) found that the [CII]/FIR deficit also persisted in their sample of five z ∼ 6 quasars detected by ALMA, and Rawle et al (2013) found a deficit for an extreme starburst SMG at z ∼ 5. Similarly, Iono et al (2006) Decarli et al (2012).…”
Section: The [Cii]-fir Deficit In Galaxiesmentioning
confidence: 83%
See 2 more Smart Citations
“…The high-z points that show a deficit in this study tended to host an AGN. Wang et al (2013a) found that the [CII]/FIR deficit also persisted in their sample of five z ∼ 6 quasars detected by ALMA, and Rawle et al (2013) found a deficit for an extreme starburst SMG at z ∼ 5. Similarly, Iono et al (2006) Decarli et al (2012).…”
Section: The [Cii]-fir Deficit In Galaxiesmentioning
confidence: 83%
“…Further X-ray analysis of SMGs estimate AGN fractions of 20-29(±7)% (Laird et al, 2010), <26±9% (Georgantopoulos et al, 2011), 14-28% and 17( +16 −6 )% . The Wang et al (2013a) work is of particular note since its sample is the ∼100 ALMA-confirmed 870µm-selected sources in CDFS with unambiguous counterparts, enabling effectively more precise measurements in both X-ray and FIR. An important follow-up to these X-ray studies of SMGs came in Alexander et al (2008).…”
Section: Agn Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen have been added to the number of z > 4 [CII] detections in the past decade (Maiolino et al 2005(Maiolino et al , 2009Iono et al 2006;Wagg et al 2010;Ivison et al 2010;De Breuck et al 2011;Cox et al 2011;Swinbank et al 2012;Venemans et al 2012;Walter et al 2012;Riechers et al 2013;Wang et al 2013;Rawle et al 2014;De Breuck et al 2014;Neri et al 2014). Many of these objects have been selected based on the presence of a luminous active galactic nuclei (AGN; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these objects have been selected based on the presence of a luminous active galactic nuclei (AGN; e.g. Maiolino et al 2005;Stacey et al 2010;Wang et al 2013), while others have been selected as starburst galaxies (e.g. Ivison et al 2010;Hailey-Dunsheath et al 2010;Stacey et al 2010;Cox et al 2011;Swinbank et al 2012;Walter et al 2012;Riechers et al 2013;Brisbin et al 2015).…”
Section: Introductionmentioning
confidence: 99%